(untitled) (Journal of the College of Basic Education, 2022)
In our tagged research “The Doctrinal Investigations in Monotheism and Prophethood between the Interpretation of Hassan Al-Bayan Al-Baysani and Bringing the Qur’an to Mind by Al-Shirazi” we explained in it: Monotheism and its branches from it (the vision of God, the creation of the Qur’an, the issue of attributes) and each branch of it we clarified evidence from the Holy Qur’an for both interpretations and what is understood Attributes of the Imamis and Ash’aris and how many are divided into each of them, then we explained the concept of prophecy and what is the difference between the Prophet and the Messenger according to both Shirazi and Balisani through Quranic evidence and what is the ruling on sending messengers to them through Quranic evidence.